2022
DOI: 10.1371/journal.ppat.1010660
|View full text |Cite
|
Sign up to set email alerts
|

A protein–protein interaction map reveals that the Coxiella burnetii effector CirB inhibits host proteasome activity

Abstract: Coxiella burnetii is the etiological agent of the zoonotic disease Q fever, which is featured by its ability to replicate in acid vacuoles resembling the lysosomal network. One key virulence determinant of C. burnetii is the Dot/Icm system that transfers more than 150 effector proteins into host cells. These effectors function to construct the lysosome-like compartment permissive for bacterial replication, but the functions of most of these effectors remain elusive. In this study, we used an affinity tag purif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 78 publications
0
11
0
Order By: Relevance
“…This result indicated that the inducible CRISPRi system could target genes essential for intracellular infection and small SCV‐specific genes. Constitutive CRISPRi knockdown of the Dot/Icm substrate CirB in C. burnetii was recently described (Fu et al, 2022 ). This shuttle vector‐based system adopts an always‐on approach using the cbu1169 promoter to drive both sgRNA and dcas9 expression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This result indicated that the inducible CRISPRi system could target genes essential for intracellular infection and small SCV‐specific genes. Constitutive CRISPRi knockdown of the Dot/Icm substrate CirB in C. burnetii was recently described (Fu et al, 2022 ). This shuttle vector‐based system adopts an always‐on approach using the cbu1169 promoter to drive both sgRNA and dcas9 expression.…”
Section: Discussionmentioning
confidence: 99%
“…The CRISPRi system was first tested by knocking down the production of the host cell essential Dot/Icm protein IcmD (Figure S1) and then by simultaneously knocking down both IcmD and the small SCV-specific protein ScvA production (39 amino acids) (Figure S2). This result indicated that the inducible CRISPRi system could target genes essential for intracel- described (Fu et al, 2022). This shuttle vector-based system adopts an always-on approach using the cbu1169 promoter to drive both sgRNA and dcas9 expression.…”
Section: Previous Attempts To Use the Dcas9 From Staphylococcus Aureu...mentioning
confidence: 99%
“…However, we cannot determine whether the detected bacteria were in the tick or on the tick, or whether pathogens or bacteria were transmitted from the tick's surface. In addition, excluding known bacterial pathogens, such as the spotted fever group rickettsia C. burnetii (Huang et al, 2021;Fu et al, 2022), a potentially new pathogen, R. cervicalis, was detected in both the blood and skin samples of patients. Although more than 10 viral families were found in ticks by RNA-seq in our previous study (Li et al, 2021), only three viruses (i.e., JMTV, BLTV4, and DTMV) could be detected in skin biopsy specimens.…”
Section: Discussionmentioning
confidence: 99%
“…This result indicated that the inducible CRISPRi system could target genes essential for intracellular infection and small SCV- specific genes. Constitutive CRISPRi knockdown of the Dot/Icm substrate CirB in C. burnetii was recently described (Fu et al, 2022). This shuttle vector-based system adopts an always on approach using the cbu1169 promoter to drive both sgRNA and dcas9 expression.…”
Section: Discussionmentioning
confidence: 99%